Doing Business 2017 : Equal Opportunity for All - World Bank Group (Washington, DC: World Bank, 2016)
Fourteenth in a series of annual reports comparing business regulation in 190 economies, Doing Business 2017 measures aspects of regulation affecting 10 areas of everyday business activity: • Starting a business • Dealing with construction permits • Getting electricity • Registering property • Getting credit • Protecting minority investors • Paying taxes • Trading across borders • Enforcing contracts • Resolving insolvency.